2014
DOI: 10.3390/rs6109930
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Coastline Changes under Human Intervention Using Multi-Temporal High-Resolution Images: A Case Study of the Zhoushan Islands, China

Abstract: Abstract:Continued sea-level rise and coastal development have led to considerable concerns on coastline changes along inhabited islands. Analysis of long-term coastline changes of islands is however limited due to unavailable data and the cost of field work. In this study, high-resolution images taken from 1970-2011 at an interval of about 10 years and topographic maps were collected to determine coastline changes and their drivers in the Zhoushan Islands, China. Results show that nearly all inhabited islands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 45 publications
2
19
0
3
Order By: Relevance
“…In line with the idea that urbanization is becoming an important factor in land use change (Olaniyi et al 2012), the impervious surface area (ISA) on the Zhoushan Archipelago increased significantly from 2006 to 2011 (Zhang et al 2013) as a result of urban construction and the development of transportation infrastructure. Zhang et al (2014) examined the coastline changes of the Zhoushan Archipelago and found noteworthy seaward (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020). "…”
Section: Discussionmentioning
confidence: 99%
“…In line with the idea that urbanization is becoming an important factor in land use change (Olaniyi et al 2012), the impervious surface area (ISA) on the Zhoushan Archipelago increased significantly from 2006 to 2011 (Zhang et al 2013) as a result of urban construction and the development of transportation infrastructure. Zhang et al (2014) examined the coastline changes of the Zhoushan Archipelago and found noteworthy seaward (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020). "…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Masselink & Rusell (2013), perairan pantai merupakan wilayah yang sangat dinamis dan sangat intensif mendapat pengaruh antropogenik. Berbagai aktivitas manusia di wilayah pantai dapat menimbulkan perubahan struktur pantai dari kondisi alam inya, baik terjadi secara alam i seperti pendangkalan dan erosi atau buatan seperti kegiatan reklamasi pantai (Zhang et al, 2014).…”
Section: Pendahuluanunclassified
“…The fractal dimension is a good parameter representing coastline characteristics, and has been often used in the study of coastlines [29,30]. The bigger the fractal dimension value, the more complex is the shape of the coastline.…”
Section: Methodsmentioning
confidence: 99%